Intra-Annual Patterns in the Benthic-Pelagic Fluxes of Dissolved and Particulate Matter - Rühl, Saskia; Thompson, Charlie E. L.; Queirós, Ana M.; Widdicombe, Stephen (Frontiers in Marine Science, 2020)
In coastal temperate environments, many processes known to affect the exchange of particulate and dissolved matter between the seafloor and the water column follow cyclical patterns of intra-annual variation. This study assesses the extent to which these individual short term temporal variations affect specific direct drivers of seafloor-water exchanges, how they interact with one another throughout the year, and what the resulting seasonal variation in the direction and magnitude of benthic-pelagic exchange. Existing data from a multidisciplinary long-term time-series from the Western Channel Observatory, UK, were combined with new experimental and in-situ data collected throughout a full seasonal cycle. These data were used to define an average year, split into five ‘periods’ (winter, pre-bloom, bloom, post-bloom and autumn) based around the known importance of pelagic primary production and hydrodynamically active phases of the year. Multivariate analyses were used to identify specific sub-sets of parameters that described the various direct drivers of seafloor-water exchanges. Both dissolved and particulate exchange showed three distinct periods of significant flux during the year, although the specific timings of these periods and the cause-effect relationships to the direct and indirect drivers differed between the two types of flux. Dissolved matter exchange was dominated by an upward flux in the pre-bloom period driven by diffusion, then a biologically induced upward flux during the bloom and an autumn downward flux. The latter was attributable to the interactions of hydrodynamic and biological activity on the seafloor. Particulate matter exchanges exhibited a strongly hydrologically influenced upward flux during the winter, followed by a biologically induced downward flux during the bloom and a second period of downward flux throughout post-bloom and autumn periods. This was driven primarily through interactions between biological activity, and physical and meteorological drivers. The integrated, holistic and quantitative data-based analysis of intra-annual variability in benthic/pelagic fluxes presented in this study in a representative temperate coastal environment, demonstrates not only the various process’ inter-connectivity, but also their relative importance to each other. Future investigations or modelling efforts of similar systems will benefit greatly from the relationships and baseline rules established in this study.